Interdialytic weight gain and fatigue in chronic kidney disease patients undergoing hemodialysis: A Correlational study - Nur Widayati; Nindy Dwi Maharani; Ana Nistiandani (KHD-Production, 2025)
Chronic Kidney Disease (CKD) has become a significant global health problem, characterized by the gradual and progressive damage to nephrons and decreased glomerular filtration rate which causes toxins in the body to accumulate and cause fatigue. One of the main problems experienced by hemodialysis patients is how to manage interdialytic weight gain (IDWG). Continuous excess extracellular fluid can cause adverse effects on the heart and respiratory function, which serves as the physiological basis for fatigue. This study aimed to analyze the relationship between IDWG and fatigue in CKD patients undergoing hemodialysis. This study used an analytical observational design with a cross-sectional approach. The sample used was 139 respondents using total sampling technique. Data collection of IDWG was conducted by a One Health digital weighing scale and Functional Assessment of Chronic Illness Therapy (FACIT) Fatigue Scale version 4 questionnaire. Data mean value IDWG 3.48% with a standard deviation of 1.72 and a median fatigue score of 26.0 with a low score of 12 and a high score of 46. Data were analyzed by using Spearman's rho correlation test with a significance level of 0.05. The results showed a weak negative relationship between IDWG and fatigue (p value <0.001 ; r = -0.385). It means that the higher the IDWG value, the lower the fatigue score, indicating that the fatigue level is more severe. This study highlights the importance of controlling IDWG to reduce fatigue levels in chronic kidney disease patients undergoing hemodialysis